2018
DOI: 10.3389/fimmu.2018.02278
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Significance and Implications of Antibody Numbering and Antigen-Binding Surface/Residue Definition

Abstract: Monoclonal antibodies are playing an increasing role in both human and animal health. Different strategies of protein and chemical engineering, including humanization techniques of non-human antibodies were applied successfully to optimize clinical performances of antibodies. Despite the emergence of techniques allowing the development of fully human antibodies such as transgenic Xeno-mice, antibody humanization remains a standard procedure for therapeutic antibodies. An important prerequisite for antibody hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 90 publications
0
61
0
Order By: Relevance
“…Abhinandan and Martin further refined the Chothia numbering scheme by making corrections, not only in the CDRs but also in the FRs. Here, we used the Martin numbering scheme to annotate the FRs and CDRs of antibodies as it was found to be suitable for structural and antibody engineering (Dondelinger et al, 2018) and it is the most recent of the presently available numbering schemes. Supplementary Table S1 summarizes the position of FR and CDR regions and the position of insertions according to the Martin numbering scheme.…”
Section: Selection Of Antibody Sequence Numbering Schemementioning
confidence: 99%
See 1 more Smart Citation
“…Abhinandan and Martin further refined the Chothia numbering scheme by making corrections, not only in the CDRs but also in the FRs. Here, we used the Martin numbering scheme to annotate the FRs and CDRs of antibodies as it was found to be suitable for structural and antibody engineering (Dondelinger et al, 2018) and it is the most recent of the presently available numbering schemes. Supplementary Table S1 summarizes the position of FR and CDR regions and the position of insertions according to the Martin numbering scheme.…”
Section: Selection Of Antibody Sequence Numbering Schemementioning
confidence: 99%
“…While the percentage of interacting residues found in the CDR3 was consistent between heavy and light chains, only half as many interacting residues mapped to CDR-H1 (14.8%) as compared to CDR-L1 (32.5%), whereas the reverse was true for CDR-H2 (36.1%) and CDR-L2 (13.9%). Since we used the Martin numbering scheme for CDR and FR annotation (see Methods), which mostly excludes germline gene residues from the CDR3, the above numbers demonstrate that germline-gene residues surrounding the CDR3 (FR3, FR4) contribute relatively little to antibody-interaction and that CDR3 paratope-epitope interaction is essentially non-germline gene residue driven (Abhinandan and Martin, 2008;Dondelinger et al, 2018). Finally, we found that paratope interacting residues correlate positively with the sites of (inferred) somatic hypermutation (SHM) (Spearman (Pearson) correlation: 0.31-0.52 (0.44-0.58), Suppl Fig.…”
Section: The Majority Of Paratope Interacting Residues Are Located Inmentioning
confidence: 99%
“…The most commonly employed method for humanization consists in grafting murine CDRs into whole human framework regions. Still, it has been demonstrated that some murine framework residues, denoted as vernier zone residues, are able to interfere in the CDR loops conformation thus affecting antibody binding affinity [38,41]. Although many methods have been reported for humanization, the immunogenicity of therapeutic antibodies is still a discussed matter [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The main differences between all antibody variable domains are content, structure, and conformations of CDR loops. Non‐CDR framework regions are mostly conserved and have a high degree of structural conservation forming a core β‐sheet structure 28 . Although several studies point out that non‐CDR regions are important for biophysical properties 29 and humanization, 30,31 their roles on affinity/specificity are underestimated 29,32 .…”
Section: Introductionmentioning
confidence: 99%
“…Back mutations on the Vernier zone can provide the desired canonical structure of CDRs to obtain restored binding affinity 36 . However, there is no study investigating the relationship between Vernier zone residues and antibody specificity 28 . Although Vernier zone residues are mostly engineered for humanization efforts to regain/improve affinity, it can be hypothesized that features of Vernier zone residues might also affect many antibody properties such as binding specificity.…”
Section: Introductionmentioning
confidence: 99%